1992
DOI: 10.1111/j.1748-0361.1992.tb00341.x
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Cost of Farm Tractor Rollover Deaths in New York

Abstract: Farm tractor rollovers account for one quarter of all fatal farm injuries, but their economic impact has not been studied previously. This study surveyed surviving family members of people killed between 1985 and 1987 in New York farm tractor rollovers and found the average expected income lost by each death was $243,615 (response rate=46%, N=12). Fatal farm tractor rollovers may cost New York more than $2 million a year in lost income. Nonfarmers account for 33 percent of these rollover deaths. These nonfarme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Studies known to our group include Kelsey [1991], who estimated the total income foregone in New York State due to fatal farm accidents at $8.6 million annually. In a separately published study, he calculated average annual income lost due to tractor rollovers in New York at more than $ 2 million [Kelsey, 1992]. Agger et al [1986] showed the relatively high costs of treating secondary infections in wounds caused by corn-harvesting machines.…”
Section: Introductionmentioning
confidence: 99%
“…Studies known to our group include Kelsey [1991], who estimated the total income foregone in New York State due to fatal farm accidents at $8.6 million annually. In a separately published study, he calculated average annual income lost due to tractor rollovers in New York at more than $ 2 million [Kelsey, 1992]. Agger et al [1986] showed the relatively high costs of treating secondary infections in wounds caused by corn-harvesting machines.…”
Section: Introductionmentioning
confidence: 99%